Gender Stereotypes in Boyd Smith’s the Story of Pocahontas and Captain John Smith: A Greimas’ Actantial Model - Supiastutik Supiastutik; Dyah Purwita WSWW; Olivia Putri Citra Ramadani (Lingua Cultura, 2023)
The research attempted to examine the contribution and relevance of structuralism as a theory, method, and paradigm, especially in the study of feminist literary criticism in the novel entitled The Story of Pocahontas and Captain John Smith. Many researchers had scrutinized the novel from various approaches, such as socio-cultural, historical political, and post-colonial studies. However, analysis using actantial models had not been conducted and reported in scholarly journals. The qualitative research utilized textual analysis that practiced a narrative semiotic approach proposed by Greimas. The research used the actantial model proposed by Greimas to evaluate the narrative’s deep structure so as to reveal gender stereotypes of male and female characters in the novel, written in 1906. Although the female character appeared as the main character, she was portrayed as sentimental, emotional, weak, and dependent on the male characters’ help. In contrast, the male characters were shown as dominant figures. They were portrayed as physically strong, rational, thoughtful, and able to prioritize the interests of the wider community and independently achieve the goals they wanted. It is found that the discussion about gender stereotypes in literary works is still relevant to be carried out, especially in literary works, because several kinds of research showcase that the portrayal of stereotyped characters has an unfavorable impact on children’s cognitive and affective development.